Synthesis of MOF Nanosheets in Hyperswollen Lyotropic Lamellar Phase. (3rd May 2019) - Omiya, Takeru; Sasaki, Koki; Uchida, Yoshiaki; Nishiyama, Norikazu
Abstract: We have synthesized very thin nanosheets (NSs) of metal-organic frameworks (MOFs) in sandwich-like reaction fields (SRFs) inside the bilayers of a hyperswollen lyotropic lamellar (HL) phase. The obtained samples were characterized by means of infrared spectroscopy, atomic force microscopy, transmission electron microscopy and X-ray diffraction measurements. The thickness and horizontal width of the MOF-NSs obtained from the synthesis in the SRFs in the HL phase are a few nanometres and several hundreds of nanometres, respectively. The accumulation and reaction of ingredients in the highly separated bilayers in the HL phase should result in a dilute aqueous suspension of very thin MOF-NSs.